Pengurusan sistem maklumat pendidikan: implikasi pengautomasian ke atas pengajaran dan kebolehgunaan data. - Zawiyah Mohammad Yusof; Mariah Lambak (Universiti Kebangsaan Malaysia, 2008)
This study seeks to identify problems face by teachers responsible in managing automated information system supplied by the Ministry of Education known as Sistem Maklumat Pengururan Pendidikan Kementerim Pelajaran (SMPP-KP). Is it true that managing the automated education information system has assert pressure in the form of additional work load which in turn agects the quality of teaching of those teachers. Time constraint (a confEict between fulfilling the need of teaching as their main task and managing the information system) has also contributed problem to teachers from giving attention to the reliability of data particularly its accuracy and validity. This resulted in discouraging the sharing of data stored in SMPP-KP. This low level of data sharing is also partly due to the fact that teachers do not have the competency in using computer, manipulating data and handling the system. The study emphasises on 5 SMPPKPS currently in used at schools. Survey method using questionnaire was adopted. The study was carried out in 2005 involving 31 schools in Melaka Tengah with 138 SMPP-KP managing teachers taken into account. Findings shows that SMPPKP teachers experienced a high level of work overload which leave negative effect on teaching though at only minimum level. It is the limited time that the teachers have to check on the data and the dificulty to acquire reliable data from the source that has contributed to the problem of data inaccuracy and validity. As a result, optimum data sharing has not taken place. It is also discovered that the level of competency of SMPP-KP teachery is only minimal despite courses being given from time to time. These teachers claimed that the courses they attended are of little help in improving their competency because the handling of SMPP-KP require more than the basic skill for using the computer. It needs the skill of manipulating the data and the database.